Pengaruh Tingkat Pendidikan, Usia, dan Motivasi Membayar Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Empiris pada Wajib Pajak Orang Pribadi di Wilayah KPP Pratama Bangkinang) - Hariyanis, Arza; Fionasari, Dwi; Armel, R. Septian (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This research was conducted at KPP Pratama Bangkinang with the aim of examining the effect of education level, age, and motivation to pay taxes on individual taxpayer compliance (an empirical study on individual taxpayers in the KPP Pratama Bangkinang area). The population in this study is WPOP, who submitted a total of 28,345. Sample determination is done using Isaac's formula to determine the number of samples because the population obtained is already known in number. And the sample taken was 268 individual taxpayers. Sampling method with a simple random sampling technique. Research variables using bound and free. Data collection in this study was done by questionnaire. The type of data used in this study is primary data. The data analysis used is multiple linear regression analysis with the help of the SPSS (Statistical Product and Service Solution) for Windows version 24 program. The conclusion of this study is that education level, age, and motivation to pay taxes have a significant effect on compliance to pay individual taxes.Keywords: WP OP Compliance, Motivation to Pay Taxes, Education Level, Age, Individual Taxpayers.